Stable isotope constraints on urban CO2 and CH4 emission sources in Montreal derived from aircraft, UAV, and ground measurements - Regina Gonzalez Moguel; Peter M.J. Douglas; Keyvan Ranjbar; Leonid Nichman; Jacob Asomaning; Quinn Dyer-Hawes; Gustavo Villarruel; Djordje Romanic; Lei Liu; Benjamin Riot—Bretêcher; Beatriz Porto Ghirardi; John Stix; et al. (Atmospheric Environment, 2026)

Multi-scale calibration strategies and minimal ground-truth requirements for soil moisture mapping on golf course fairways with portable L-band passive radiometry - Madan Sapkota; Elia Scudiero; Weston W. Floyd; Benjamin G. Wherley; Jacob O. Winger; David S. McCall; Travis L. Roberson; Elisabeth Kitchin; Chase M. Straw (Precision Agriculture, 2026)
Purpose L-band passive microwave radiometry enables reliable soil moisture retrieval from satellites but at spatial resolutions too coarse for precision irrigation. Portable near-ground L-band radiometers offer a high-resolution alternative. This study evaluated a Portable L-band Radiometer (PoLRa) for estimating volumetric water content (VWC), comparing manufacturer-calibrated estimates with data-driven calibration approaches and quantifying ground-truth requirements. Methods Field experiments were conducted at four golf courses in Texas and Virginia from August 2023 to March 2025, with three fairways per site across 17 surveys. Brightness temperature was collected using a vehicle-mounted PoLRa, and ground-truth VWC was measured at 11 to 12 locations per fairway using time domain reflectometry (TDR). Model performance was evaluated across 5,000 calibration and evaluation iterations, with three samples per fairway. Site-dependent models employed analysis of covariance (ANOCOVA), and minimal calibration analyses evaluated ground-truth sample sizes ( N = 2 to 8) per fairway. Results Manufacturer-calibrated PoLRa estimates showed weak agreement with TDR (R² = 0.40). Data-driven site-independent models failed to maintain accuracy across locations and times (RMSE > 0.089 m 3 m − 3 ). Site-dependent models substantially improved performance (R² = 0.727 to 0.757; RMSE = 0.052 to 0.056 m 3 m − 3 ), with the global ANOCOVA model balancing accuracy and scalability. Minimal calibration analysis showed three ground-truth samples per fairway achieved acceptable errors (RMSE Conclusion Through site-dependent calibration, PoLRa can provide reliable soil moisture estimates, enabling scalable soil moisture mapping for precision irrigation and turfgrass management.

Simulating coastal hydrodynamics: the role of seagrass in climate adaptation - Luciana Villa Castrillón; Johannes Pein; Benjamin Jacob; Thomas H. Badewien; Vicente Gracia García; Agustín Sánchez-Arcilla; Joanna Staneva (Ocean Dynamics, 2026)
This study investigates how future hydrodynamic and sediment transport may evolve in the Jade Bay, located in the southern Wadden Sea, by analyzing a historical baseline (1999–2003) as well as future projections (2090–2099) under the high-emission RCP8.5 scenario. We conducted 10-year simulations using the Semi-Implicit Cross-Scale Hydroscience Integrated System Model (SCHISM) for three distinct sea-level rise (SLR) trajectories corresponding to the 5th, 50th, and 95th percentiles of projected SLR to capture a realistic range of climate variability. Return periods of residual water levels were estimated to characterize extreme events and analyze the impact of SLR on the hydrodynamics and sediment transport. To assess ecological changes, we used European Nature Information System (EUNIS) habitat maps for the historical and projected periods. This allowed us to make a spatially explicit comparison of habitat distribution over time and highlight potential shifts in coastal ecosystems under changing hydrodynamic conditions. The results show that future SLR intensifies flow velocities and bed shear stress, increasing erosion risk and destabilizing sediments, particularly in high-energy zones. Habitat mapping revealed a contraction of intertidal areas and salt marshes by up to 62% and an expansion of aquatic habitats by up to 28%, with important implications for ecosystem services. Numerical experiments incorporating seagrass as a nature-based solution demonstrated their capacity to attenuate wave heights by up to 20% and decrease erosion by up to 60%, highlighting their potential role in enhancing coastal resilience under future sea-level rise scenarios.

On the genesis and development of coastal submesoscale eddies in the Northwestern Black Sea shelf - Carolina B. Gramcianinov; Emil V. Stanev; Benjamin Jacob; Joanna Staneva (Ocean Modelling, 2026)

Comparative evaluation of AfriTEC, IRI-2020, and NeQuick-2 models over the African region - Benjamin Wisdom Joshua; Jacob Olusegun Adeniyi; Shola John Adebiyi; Yushau Muhammad Sulaiman; Abdulrahim R. Bola; Daniel Okoh; Babatunde A. Rabiu; Lucky Igbinosun; Olufemi Adebesin Babatunde; Gopi Seemala (Advances in Space Research, 2026)

Analysis of urban greenhouse gas dispersion for downtown Montréal using computational fluid dynamics and field measurements - Quinn Dyer-Hawes; Djordje Romanic; Yi Huang; John R. Gyakum; Peter M.J. Douglas; Lei Liu; Benjamin Riot–Bretêcher; Regina Gonzalez Moguel; Jacob Asomaning; John Stix; Gustavo Villarruel; Margaret Kalacska; et al. (Atmospheric Pollution Research, 2026)

Advancing conservation through virtual livestock fencing - Drew E. Bennett; Travis Brammer; Jerod A. Merkle; Kurt T. Smith; Shawn Regan; Temple Stoellinger; Arthur Middleton; Kristin Barker; Jacob P. Hochard; Patrick E. Lendrum; Erin Welty; Craig Benjamin; et al. (Biological Conservation, 2026)

Experimental study of particle velocity fields and gas-phase temperatures in oxy-fuel biomass combustion in a semi-industrial swirl-stabilized combustion chamber - Janik Hebel; Matthias Bonarens; Dominik König; Jacob Münzenberger; Bernd Epple; Benjamin Böhm; Steven Wagner; Andreas Dreizler (Fuel, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Shortleaf Pine (Pinus echinata): Management Challenges, Knowledge Gaps, and Opportunities for an Unsung Species - Benjamin O. Knapp; Jacob Fraser; Joanne Baggs; Vikram E. Chhatre; David Clabo; Connor D. Crouch; Daniel C. Dey; Shaik M. Hossain; Steven B. Jack; John M. Kabrick; Kathryn R. Kidd; Steven McNulty; et al. (Journal of Forestry, 2026)
Shortleaf pine has the broadest range of the southern pine species, occurring in 22 states and extending north into New Jersey, Pennsylvania, and New York (Staten Island). Shortleaf pine has been understudied compared to loblolly pine and longleaf pine, typically favored for timber production and conservation value, respectively. The extensive range of shortleaf pine contributes to a high degree of variability within and among its ecosystems and contributes to the need to understand regional context in considering its ecology and management. The goal of this paper is to review and synthesize the state-of-knowledge on shortleaf pine ecosystems, emphasizing the importance of variation across its range in identifying management challenges and opportunities. We discuss the variation in growing conditions that occur across the geographic range, shortleaf pine natural community groups, and contemporary shortleaf pine forest types that occur on the landscape. We provide a review of the state-of-knowledge for topics related to shortleaf pine management, including its fire ecology, genetic considerations, economics, and others. Finally, we synthesize these into key considerations and highlight regionally specific management challenges and opportunities.

Evaluation of seagrass as a nature-based solution for coastal protection in the German Wadden Sea under end of the century sea level rise projections - Benjamin Jacob; Johannes Pein; Joanna Staneva (Ocean Dynamics, 2026)
Climate change, along with sea-level rise and shifting hydrodynamics, threatens coastal systems such as the Wadden Sea. At the same time, nature-based solutions (NbS) have gained prominence in coastal protection, recognizing the buffering role of vegetation such as seagrass. This study evaluates hypothetical seagrass meadow extension scenarios as NbS, assessing their potential to mitigate coastal hazards under present and future climate conditions. Time-slice simulations for the years 1997 and 2090 were conducted using the unstructured-grid SCHISM modeling framework, which couples hydrodynamics, wave action, sediment dynamics, and a vegetation module representing first-order seagrass effects on flow and turbulence. Pairwise simulations under the RCP8.5 scenario with and without vegetation were conducted to quantify attenuation of currents, wave energy, bottom stress, and sediment concentrations. Results show that despite a 20% decline in relative attenuation efficiency under sea-level rise, seagrass meadows retain substantial damping capacity. Wave heights were reduced by 30% in shallow areas, with even greater absolute reductions in deeper zones of enhanced wave activity. Bottom stress attenuation frequently exceeded 60%, accompanied by lower near-bed sediment concentrations. Although limited to hydrodynamics and a time-slice approach, the study points to potential shifts in seagrass attenuation efficiency under SLR, underscoring the role of sediment accumulation balancing net water column increase for a maintained bathymetric control, advocating for seagrass-based nature-based solutions in coastal adaptation.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

A framework for morphological impact assessment of a small sandy beach under climate What-If Scenarios and Nature-based Solutions - Douglas Vieira da Silva; Wei Chen; Benjamin Jacob; Carolina Gramcianinov; Nam Thanh Pham; Marcel Ricker; Kelli Johnson; Johannes Pein; Joanna Staneva (Journal of Environmental Management, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Honestly exaggerated: howler monkey roars are reliable signals of body size and behaviourally relevant to listeners - Jacob C. Dunn; Eloise Pedersen; Holly Farmer; Phillipa Dobbs; W. Tecumseh Fitch; David Reby; Benjamin Charlton (Animal Behaviour, 2026)

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

The frailty mortality link in people with chronic diseases pertaining to 13 body organ systems: findings from the UK Biobank study - Justine Dastouet; Aurore Fayosse; Louis Jacob; Archana Singh-Manoux; Séverine Sabia; Benjamin Landré (GeroScience, 2025)
Frailty in older adults, particularly those with chronic diseases, has a robust association with risk of mortality, but whether this is the case in middle-aged adults is unclear. We examined the frailty-mortality association in middle-aged adults with chronic diseases and multimorbidity. Data on Fried’s frailty phenotype (robust, prefrail, frail) and 47 chronic diseases, mapped to 13 body organ systems, was available on 230,960 participants of the UK Biobank study (mean age 57.8, range 38.0–72.0). The mortality follow-up was 13.3 (± 2.1) years, and associations with mortality were examined using Cox regression, adjusted for socio-demographic factors and health behaviours. Compared to the robust group, frailty (HR, 2.32 (95% confidence intervals, 2.21; 2.43)) and prefrailty (1.35 (1.31; 1.39)) in those with diseases in any body organ system had a higher risk of mortality. Frailty was associated with a higher mortality risk for all 13 groups (all p < 0.01); estimates ranged from 2.25 (2.12; 2.39) for circulatory system diseases to 2.97 (2.60; 3.39) for the eye system. The same was the case for prefrailty; estimates ranged from 1.33 (1.23; 1.43) to 1.61 (1.03; 2.51). Between 19 and 34% of the mortality risk in the 13 disease groups could potentially be explained by frailty/prefrailty. Frailty ( p < 0.01) and prefrailty ( p < 0.01) had stronger associations with mortality in those with diseases affecting multiple organ systems. These findings highlight the importance of frailty in middle-aged adults with chronic diseases, suggesting that a third of the excess risk of mortality could potentially be addressed by improving frailty status.

Role of age in the association of chronic conditions and multimorbidity with incident ADL disability: multicohort analyses of 108,810 adults - Benjamin Landré; Aurore Fayosse; Louis Jacob; Mikaela Bloomberg; Ian Danilevicz; Frank van der Heide; Séverine Sabia; Archana Singh-Manoux (GeroScience, 2025)
Chronic conditions and multimorbidity are increasingly prevalent in ageing populations, and their impact on disability remains poorly understood. This study investigated the association of chronic conditions and multimorbidity at ages 50, 60, 70, and 80 years with the subsequent onset of disability. Data from 108,810 participants (54% women, mean age 61.2 ± 9.8 at baseline) from the Health and Retirement Study, the English Longitudinal Study of Ageing, and the Survey of Health, Ageing, and Retirement in Europe were used. The number of chronic conditions was determined from a list of eight conditions. Cox regression was used to examine the incidence of disability in activities of daily living (ADL). ADL disability per 1000 person-years was 14.2 (13.7, 14.7) at age 50, 22.4 (21.9, 22.9) at age 60, 34.3 (33.4, 35.1) at age 70, and 67.6 (65.6, 69.6) at age 80. Having one chronic condition at age 50 was associated with a hazard ratio (HR) for ADL disability of 1.50 (1.42, 1.58) and 1.22 (1.13, 1.42) at age 80. For individuals with three or more chronic conditions, the HRs were 3.05 (2.79, 3.33) at age 50 and 1.74 (1.61, 1.87) at age 80. Analysis of population attributable fraction suggests that between 5.0 and 29.4% of incident disability, depending on the intervention scenarios and age at onset of chronic diseases, could be reduced by acting on chronic diseases. Chronic conditions and multimorbidity demonstrated a strong association with the onset of ADL disability, highlighting the need for early intervention to mitigate future disability risks.

Assessment of the rock fall geo-hazards of the sub-vertical rock cliffs behind the Mortuary Temple of Hatshepsut (MTH), Luxor, Egypt - Mostafa Ezzy; Benjamin Jacobs; Michael Krautblatter; Christian U. Grosse; Hany Helal; Mohamed Ismael (Engineering Geology, 2025)

Tailoring Mg-MOF-74 for trace CO₂ capture by morphological tuning and piperazine functionalization - Qiao Liu; Shraavya Rao; John Matteson; Cassandra Gates; Nina S. Pappas; Kate Chen; Benjamin Stein; Xiaojing Wang; Piotr Zelenay; Rajinder P. Singh; Jacob S. Spendelow (Chemical Engineering Journal, 2025)

The role of litter in enhancing water availability to Bromus tectorum L. (cheatgrass) changes according to soils - Brian Morra; Beth A. Newingham; Benjamin W. Sullivan; Jacob C. Ellis; Camie M. Dencker (Plant and Soil, 2025)

Tidal impacts on volume and salt transport through the Strait of Hormuz and on Persian Gulf salinity - Seyed Taleb Hosseini; Emil Stanev; Johannes Pein; Corinna Schrum; Benjamin Jacob (Ocean Dynamics, 2025)
This study uses high-resolution numerical modelling to quantify the impact of tidal forcing on water and salt transport through the Strait of Hormuz (SOH) and its influence on salinity distribution in the Persian Gulf (PG). By resolving high-frequency dynamics, we evaluate exchange flow rates under both tidal and nontidal conditions. Two key findings emerge: (1) Tides significantly enhance mixing within the strait, increasing the salinity of inflowing waters. This reduces the freshening effect of the Oman Sea on the PG and elevates the PG’s mean salinity by over 0.8 psu, thereby strengthening the horizontal salinity gradient between the PG and the Oman Sea. (2) Tidal oscillations more than double the annual mean inflow-outflow rates through the SOH from approximately ± 0.25 Sv in the nontidal model to about ± 0.54 Sv under tidal conditions. Three competing mechanisms dominate the net salt transport at the SOH: (i) Seaward flux from shear dispersion, driven by horizontal salinity gradients; (ii) Minor seaward flux from tidal pumping, resulting from negative covariance between tidal velocity and salinity over annual scales; (iii) Landward advective flux, associated with net landward volume transport, which is typical of inverse estuaries. Tidal forcing enhances the seaward salt flux via shear dispersion. Furthermore, tidal mixing is vigorous throughout the PG, with the advection-to-baroclinicity ratio consistently exceeding 0.5 on a logarithmic scale and surpassing 1 in coastal areas. Tides are a critical driver of horizontal mixing between evaporative, high-salinity coastal waters and fresher, offshore waters, significantly shaping the PG’s salinity distribution.

Effect of seasonal and geographical location on the secondary metabolic contents of Artemisia afra and Artemisia annua. Anti- plasmodial properties - Lahngong Methodius Shinyuy; Ledoux Allison; Olivia Jansen; Palmaerts Benjamin; Hallot Eric; E. Loe Gisèle; Ghogomu Stephen; Souopgui Jacob; Frédérich Michel (Phytochemistry Letters, 2025)

Correction to: Incremental efficacy systematic review and meta-analysis of psilocybin-for-depression RCTs - Nicholas C. Borgogna; Tyler Owen; Dan Petrovitch; Jacob Vaughn; David A. L. Johnson; Louis A. Pagano; Stephen L. Aita; Benjamin D. Hill (Psychopharmacology, 2025)

Incremental efficacy systematic review and meta-analysis of psilocybin-for-depression RCTs - Nicholas C. Borgogna; Tyler Owen; Dan Petrovitch; Jacob Vaughn; David A. L. Johnson; Louis A. Pagano; Stephen L. Aita; Benjamin D. Hill (Psychopharmacology, 2025)
Rationale Psilocybin is a potentially paradigm-shifting depression intervention. We conducted a systematic review and meta-analysis of psilocybin-for-depression randomized controlled trials (RCTs). Objectives Systematically assess harm reporting, risk of bias, action mechanism specification, and incremental therapeutic effect sizes in the psilocybin-for-depression RCT literature. Methods Assessed databases included PsycINFO, CINAHL, Embase, Medline, Web of Science, and Scopus. Search terms “Psilocybin” or “Psychedelic” were paired with “Depression”, and "Randomized Controlled Trial" or “RCT”. Results We identified k = 9 RCTs ( k = 10 subgroups) involving n = 602 participants (56% psilocybin). Five studies had low/very low harm quality reporting, opposed to two with high. Most studies demonstrated a high risk of bias. Therapeutic mechanisms of action (MoAs) were discussed in varying detail but rarely assessed in original publications. Psilocybin was moderately superior to controls at reducing depression ( g = 0.62; 95% CI = 0.27, 0.98). Effects were heterogenous (τ = .47). Smaller studies evidenced stronger effects that favored psilocybin (Egger’s b 0 = 3.63, p = .014). Almost all studies documented financial conflicts of interests. Conclusion Psilocybin demonstrates significant depression reduction relative to controls. However, researchers, clinicians, and stakeholders should consider several contextual factors. Effects were moderate and attenuated in larger and better-controlled studies. Harms reporting and risk of bias was high, though partly driven by unique challenges of psilocybin research. MoAs were variably specified but rarely assessed; suggesting it is unclear how depression is reduced. We advise researchers conduct RCTs with active control conditions, larger samples, and include MoA assessments. Independent RCTs from researchers without financial conflicts of interest are needed.

Can Solar‐Powered Irrigation Systems Naturally Meet Crop Water Requirements? Proof of Concept From a Case Study in Sub‐Saharan Africa - Eric Oppong Danso; Christiana Dietzen; William Akortey; Bernard Kwabena Boadi Mensah; Peter Bilson Obour; John Bright Amoah Nyasapoh; Ebenezer Agyapong; Elorm Grace Ayayi; Nana Oduro Osei Bonsu; Michael Osei Adu; Emmanuel Arthur; Jacob Ulzen; et al. (Irrigation and Drainage, 2025)
Irrigation scheduling is crucial for ensuring precise water delivery to crops. However, in many sub‐Saharan African irrigation schemes, water is applied without considering crop water needs, resulting in low crop water productivity and low yields. Solar‐powered irrigation systems can automatically meet these needs by utilizing solar radiation, which drives both evapotranspiration and solar panel power production for pumping. This study aimed to integrate irrigation scheduling into a solar‐driven irrigation system and assess the impact of meteorological variables on reference evapotranspiration (ET o ) in Ghana. A 50‐watt solar panel powered a 12‐V submersible pump, with a flow meter installed on the outlet pipe for hourly volume of water pumped (VWP) data readings. These data were used to examine correlations between solar radiation (R s ) and ET o , as well as between R s and VWP. Partial correlation analyses were used to assess the relative influences of R s , wind speed (U 2 ), relative humidity (RH) and air temperature (T air ) on ET o across 10 locations in Ghana's agroecological zones. The study revealed a strong linear correlation between the hourly R s and ET o ( R 2 > 0.9) and between the hourly R s and VWP ( R 2 = 0.8). The VWP was sufficient to meet crop‐water demand year‐round. Solar radiation was consistently the primary meteorological factor influencing ET o in Ghana.

Statistical spatial downscaling of significant wave height in a regional sea from the global ERA5 dataset - Bing Yuan; Marcel Ricker; Wei Chen; Benjamin Jacob; Nam Thanh Pham; Joanna Staneva (Ocean Engineering, 2025)

Adsorption of MC-LR enabled by customizable 3D printed graphene-coated structures - Justin D. Puhnaty; Jacob M. Lalley; Alan J. Kennedy; Jaylen A. Davis; Angela M. Evans; Sarah Grace Zetterholm; Connor C. Clark; Jesse L. Roberts; Christopher S. Griggs; Benjamin S. Magbanua (Journal of Environmental Chemical Engineering, 2025)

Seamless integration of the land–ocean continuum: the complex interplay of wave-induced processes and estuarine influences - Thao Thi Nguyen; Joanna Staneva; Antonio Bonaduce; Benjamin Jacob; Johannes Pein (Ocean Dynamics, 2025)
The study focused on the seamless integration of the land–ocean continuum, establishing a connection between the estuarine and coastal model and the regional ocean model. The integration of models that cover the land–ocean connection remains a significant challenge, as it is essential to provide a more realistic representation of estuarine flows. Such flows facilitate the transport of freshwater and salinity from the land into the coastal ocean through estuaries, where they mix with seawater flows. These mixed water masses exert a discernible influence on local dynamics, particularly regarding water stratification and circulation patterns. The interplay of wave-induced processes and estuarine influences in the coastal German Bight was quantified through comprehensive sensitivity experiments. The incorporation of high-resolution estuarine salinity data into land–ocean continuum models enhances their accuracy, enabling a more precise representation of estuarine flows and their impact on coastal simulations. The realistic representation of estuarine fluxes has a significant impact on ocean dynamics, as demonstrated by alterations to water stratification and salinity fronts along the German Bight coast. Our findings underscore the pivotal role of high-frequency freshwater discharges in modulating coastal salinity and water levels, especially during extreme flood events. The study emphasizes the necessity of incorporating wave effects and estuarine dynamics to achieve an accurate simulation of oceanographic processes in the German Bight. The integration of these processes into the regional ocean framework enhances the representation of estuarine inflows, offering a more realistic simulation of coastal environments. This is critical for effective management of coastal systems and for developing resilient strategies. These findings have significant implications for enhancing coastal forecasting systems, understanding the influence of extreme events, and guiding future research into long-term coastal dynamics under different climatic conditions. Graphical abstract

Early developmental shifts in root exudation profiles of five Zea mays L. genotypes - Benjamin D. Hafner; Olivia Pietz; William L. King; Jacob B. Scharfetter; Taryn L. Bauerle (Plant Science, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Review of bio-based wood fiber insulation for building envelopes: Characteristics and performance assessment - Liam O’Brien; Ling Li; Wilhelm Friess; Jacob Snow; Benjamin Herzog; Shane O’Neill (Energy and Buildings, 2025)

Fuel accumulation shapes post-fire fuel decomposition through soil heating effects on plants, fungi, and soil chemistry - Jacob R. Hopkins; Tatiana A. Semenova-Nelsen; Jean M. Huffman; Neil J. Jones; Kevin M. Robertson; William J. Platt; Benjamin A. Sikes (Science of The Total Environment, 2025)

After the n10: late oVEMP peaks in patients with unilateral vestibular loss and healthy volunteers - Alyssa C. Dyball; Xiao Ping Wu; Belinda Y. C Kwok; Chao Wang; Benjamin Nham; Jacob M. Pogson; Jonathan H. K. Kong; Rachael L. Taylor; Konrad P. Weber; Miriam S. Welgampola; Sally M. Rosengren (Experimental Brain Research, 2025)

Site‐Specific Nutrient Data Reveal the Importance of Soils in Driving the Mycorrhizal Make‐Up of Woody Vegetation Worldwide - Xiaobin Hua; Christopher H. Lusk; Ian A. Dickie; Stephen Adu‐Bredu; Kathryn J. Allen; Viviana Araus; Laurent Augusto; Pavel Barsukov; David Bauman; Félix Brédoire; David F. R. P. Burslem; James W. Dalling; et al. (Global Ecology and Biogeography, 2025)
Aim Arbuscular mycorrhizas (AM) and ectomycorrhizas (ECM) have different impacts on nutrient cycling, carbon storage, community dynamics and enhancement of photosynthesis by rising CO 2 . Recent global analyses have concluded that patterns of AM/ECM dominance in forests worldwide are shaped by climate, with soil nutrients contributing negligible additional explanatory power. However, their reliance on nutrient data from GIS surfaces masks important local influences of parent material, topography and soil age on soil nutrient status. We asked if use of site‐specific nutrient data reveals a more important role for nutrients. Time Period Present day. Location Global dataset comprising 703 sites, encompassing forests, savanna/woodlands, shrublands and deserts on all continents except Antarctica. Taxa Studied Arborescent plants, including angiosperms, gymnosperms and tree ferns. Methods Generalised Additive Models for Location, Scale and Shape (GAMLSS) to determine the effects of climate variables, soil nitrogen and soil phosphorus on the proportional representation of ECM and of non‐mycorrhizal species (NM) in woody vegetation. Results GAMLSS showed a strong negative relationship of ECM representation with mean annual temperature (MAT), and a strong negative relationship with soil total nitrogen. NM representation was highest on dry sites and phosphorus‐poor sites. Reanalysis showed that GIS‐derived soil nutrient data had less explanatory power than site‐specific nutrient data, and resulted in poorer model fits. Conclusions Our results support the long‐held belief that soil nutrients as well as climate influence the relative fitness of different mycorrhizal syndromes worldwide, and demonstrate the value of using site‐specific nutrient data. Soil nutrients should be considered when predicting the impact of climate change on the mycorrhizal composition of vegetation and resulting shifts in ecosystem processes.

A Systematic Review of tACS Effects on Cognitive Functioning in Older Adults Across the Healthy to Dementia Spectrum - Jacob D. Kraft; Benjamin M. Hampstead (Neuropsychology Review, 2024)

A benchmark dataset and workflow for landslide susceptibility zonation - Massimiliano Alvioli; Marco Loche; Liesbet Jacobs; Carlos H. Grohmann; Minu Treesa Abraham; Kunal Gupta; Neelima Satyam; Gianvito Scaringi; Txomin Bornaetxea; Mauro Rossi; Ivan Marchesini; Luigi Lombardo; et al. (Earth-Science Reviews, 2024)

Molecular modeling of reactive systems with REACTER - Jacob R. Gissinger; Benjamin D. Jensen; Kristopher E. Wise (Computer Physics Communications, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Investigation of the 2010 rock avalanche onto the regenerated glacier Brenndalsbreen, Norway - Siri H. Engen; Marthe Gjerde; Thomas Scheiber; Gernot Seier; Hallgeir Elvehøy; Jakob Abermann; Atle Nesje; Stefan Winkler; Kristine F. Haualand; Denise C. Rüther; Alexander Maschler; Benjamin A. Robson; et al. (Landslides, 2024)
Rock avalanches onto glaciers are rare in Norway. Here, we examine a rock avalanche that spread onto the regenerated Brenndalsbreen, an outlet glacier from Jostedalsbreen ice cap. The rock avalanche is intriguing in that limited information exists with respect to the exact time of failure, location of detachment area, and preparatory and triggering processes. Based on an analysis of ice stratigraphy and photographic documentation, we assess that the event happened between mid-March and June 4, 2010. A potential triggering factor could have been heavy snow and rainfall combined with above freezing air temperatures on March 18–19, 2010. We use digital terrain models to determine that the detachment area is at an almost vertical rock slope in a narrow gorge above Lower Brenndalsbreen. The deposit volume is estimated to 0.130 ± 0.065 Mm 3 , and the H / L ratio and fahrböschung are 0.45 and 24°, respectively. We apply a Voellmy flow model to confirm the detachment location and volume estimate by producing realistic runout lengths. Although glacial debuttressing may have been a likely preparatory process, the detachment area was exposed for 45–70 years before the rock avalanche occurred. The supraglacial rock avalanche debris was separated into two branches with a distinct melt-out line across the glacier. The debris reached the glacier front in 2019 and 2020, where it started being deposited proglacially while Lower Brenndalsbreen kept receding. The 2010 Brenndalsbreen rock avalanche may not be a unique event, as deposits constituting evidence of an old rock avalanche are currently melting out at the glacier front.

What-if nature-based storm buffers on mitigating coastal erosion - Wei Chen; Joanna Staneva; Benjamin Jacob; Xavier Sánchez-Artús; Andreas Wurpts (Science of The Total Environment, 2024)

Mobilization rates of landslides in a changing tropical environment: 60-year record over a large region of the East African Rift - Arthur Depicker; Gerard Govers; Liesbet Jacobs; Matthias Vanmaercke; Judith Uwihirwe; Benjamin Campforts; Désiré Kubwimana; Jean-Claude Maki Mateso; Toussaint Mugaruka Bibentyo; Louis Nahimana; Benoît Smets; Olivier Dewitte (Geomorphology, 2024)

Isolation and characterization of Iron-Manganese oxidizing bacteria from Gikondo urban marshland, Rwanda - Benjamin Manirakiza; Diane Mutumwinka; Jean Pierre. Munyampundu; Emery Shami; Colores Uwamariya; Jacob Souopgui; Antoine Nsabimana (Sustainable Water Resources Management, 2024)

Predicting spring phenology in deciduous broadleaf forests: NEON phenology forecasting community challenge - Kathryn I. Wheeler; Michael C. Dietze; David LeBauer; Jody A. Peters; Andrew D. Richardson; Arun A. Ross; R. Quinn Thomas; Kai Zhu; Uttam Bhat; Stephan Munch; Raphaela Floreani Buzbee; Min Chen; et al. (Agricultural and Forest Meteorology, 2024)

Senolytic treatment does not mitigate oxidative stress-induced muscle atrophy but improves muscle force generation in CuZn superoxide dismutase knockout mice - Agnieszka K. Borowik; Marcus M. Lawrence; Frederick F. Peelor; Katarzyna M. Piekarz; Abby Crosswhite; Arlan Richardson; Benjamin F. Miller; Holly Van Remmen; Jacob L. Brown (GeroScience, 2024)

Holocene warming of alpine rockwalls decreased rockwall erosion rates - Daniel Draebing; Till Mayer; Benjamin Jacobs; Steven A. Binnie; Miriam Dühnforth; Samuel T. McColl (Earth and Planetary Science Letters, 2024)

Spatial asynchrony and cross‐scale climate interactions in populations of a coldwater stream fish - George P. Valentine; Xinyi Lu; Evan S. Childress; C. Andrew Dolloff; Nathaniel P. Hitt; Matthew A. Kulp; Benjamin H. Letcher; Kasey C. Pregler; Jacob M. Rash; Mevin B. Hooten; Yoichiro Kanno (Global Change Biology, 2024)
Climate change affects populations over broad geographic ranges due to spatially autocorrelated abiotic conditions known as the Moran effect. However, populations do not always respond to broad‐scale environmental changes synchronously across a landscape. We combined multiple datasets for a retrospective analysis of time‐series count data (5–28 annual samples per segment) at 144 stream segments dispersed over nearly 1,000 linear kilometers of range to characterize the population structure and scale of spatial synchrony across the southern native range of a coldwater stream fish (brook trout, Salvelinus fontinalis ), which is sensitive to stream temperature and flow variations. Spatial synchrony differed by life stage and geographic region: it was stronger in the juvenile life stage than in the adult life stage and in the northern sub‐region than in the southern sub‐region. Spatial synchrony of trout populations extended to 100–200 km but was much weaker than that of climate variables such as temperature, precipitation, and stream flow. Early life stage abundance changed over time due to annual variation in summer temperature and winter and spring stream flow conditions. Climate effects on abundance differed between sub‐regions and among local populations within sub‐regions, indicating multiple cross‐scale interactions where climate interacted with local habitat to generate only a modest pattern of population synchrony over space. Overall, our analysis showed higher degrees of response heterogeneity of local populations to climate variation and consequently population asynchrony than previously shown based on analysis of individual, geographically restricted datasets. This response heterogeneity indicates that certain local segments characterized by population asynchrony and resistance to climate variation could represent unique populations of this iconic native coldwater fish that warrant targeted conservation. Advancing the conservation of this species can include actions that identify such priority populations and incorporate them into landscape‐level conservation planning. Our approach is applicable to other widespread aquatic species sensitive to climate change.

Invasive plant management in eastern North American Forests: A systematic review - Lauren S. Pile Knapp; David R. Coyle; Daniel C. Dey; Jacob S. Fraser; Todd Hutchinson; Michael A. Jenkins; Christel C. Kern; Benjamin O. Knapp; Dacoda Maddox; Cornelia Pinchot; G. Geoff Wang (Forest Ecology and Management, 2023)

Growth response of oaks to insect defoliation: Immediate and intermediate perspectives - Torben Hilmers; Benjamin M.L. Leroy; Soyeon Bae; W. Andreas Hahn; Sophia Hochrein; Martin Jacobs; Hannes Lemme; Jörg Müller; Gerhard Schmied; Wolfgang W. Weisser; Hans Pretzsch (Forest Ecology and Management, 2023)

Psychometric Properties of Computerized Cognitive Tools and Standard Neuropsychological Tests Used to Assess Sport Concussion: A Systematic Review - Kristin Wilmoth; Benjamin L. Brett; Natalie A. Emmert; Carolyn M. Cook; Jeffrey Schaffert; Todd Caze; Thomas Kotsonis; Margaret Cusick; Gary Solomon; Jacob E. Resch; C. Munro Cullum; Lindsay D. Nelson; et al. (Neuropsychology Review, 2023)

KAT6A mutations in Arboleda-Tham syndrome drive epigenetic regulation of posterior HOXC cluster - Meghna Singh; Sarah J. Spendlove; Angela Wei; Leroy M. Bondhus; Aileen A. Nava; Francisca N. de L. Vitorino; Seth Amano; Jacob Lee; Gesenia Echeverria; Dianne Gomez; Benjamin A. Garcia; Valerie A. Arboleda (Human Genetics, 2023)
Arboleda-Tham Syndrome (ARTHS) is a rare genetic disorder caused by heterozygous, de novo mutations in Lysine(K) acetyltransferase 6A ( KAT6A) . ARTHS is clinically heterogeneous and characterized by several common features, including intellectual disability, developmental and speech delay, and hypotonia, and affects multiple organ systems. KAT6A is the enzymatic core of a histone–acetylation protein complex; however, the direct histone targets and gene regulatory effects remain unknown. In this study, we use ARTHS patient ( n = 8) and control ( n = 14) dermal fibroblasts and perform comprehensive profiling of the epigenome and transcriptome caused by KAT6A mutations. We identified differential chromatin accessibility within the promoter or gene body of 23% (14/60) of genes that were differentially expressed between ARTHS and controls. Within fibroblasts, we show a distinct set of genes from the posterior HOXC gene cluster ( HOXC10 , HOXC11 , HOXC-AS3 , HOXC-AS2 , and HOTAIR ) that are overexpressed in ARTHS and are transcription factors critical for early development body segment patterning. The genomic loci harboring HOXC genes are epigenetically regulated with increased chromatin accessibility, high levels of H3K23ac, and increased gene–body DNA methylation compared to controls, all of which are consistent with transcriptomic overexpression. Finally, we used unbiased proteomic mass spectrometry and identified two new histone post-translational modifications (PTMs) that are disrupted in ARTHS: H2A and H3K56 acetylation. Our multi-omics assays have identified novel histone and gene regulatory roles of KAT6A in a large group of ARTHS patients harboring diverse pathogenic mutations. This work provides insight into the role of KAT6A on the epigenomic regulation in somatic cell types.

Restoration ecology through the lens of coexistence theory - Lauren M. Hallett; Lina Aoyama; György Barabás; Benjamin Gilbert; Loralee Larios; Nancy Shackelford; Chhaya M. Werner; Oscar Godoy; Emma R. Ladouceur; Jacob E. Lucero; Christopher P. Weiss-Lehman; Jonathan M. Chase; et al. (Trends in Ecology & Evolution, 2023)

Evaluation of seagrass as a nature-based solution for coastal protection in the German Wadden Sea - Benjamin Jacob; Tobias Dolch; Andreas Wurpts; Joanna Staneva (Ocean Dynamics, 2023)
Global climate change increases the overall risks for coastal flooding and erosion. Meanwhile, nature-based solutions (NbS) are increasingly becoming a focus of coastal protection measures to improve the climate adaptability. In this study, the present and potential future role of seagrass in coastal risk reduction strategies were explored for the highly energetic Wadden Sea area of the German Bight. The methodology in this study combined seagrass coverage data ( Zostera marina and Zostera noltei ) obtained by field surveys and what-if scenario simulations using the SCHISM unstructured grid model framework, coupling hydrodynamics, waves, sediments, and a seagrass module. The results suggest that the introduction of seagrass meadows locally can reduce both current velocities and significant wave heights in the order of up to 30 $$%$$ % in the deeper areas and above 90 $$%$$ % in the shallow areas. Reduction in bottom shear stress of a similar relative magnitude significantly reduced sediment mobilisation on the order of 2 g/L in the 95th quantile of bottom layer sediment concentrations. Effectively altering hydromorphodynamic conditions favouring sediment accumulation, seagrass expansion could help tidal flats height growths to keep up with SLR, thus further maintaining the bathymetry-induced tidal dampening and lowering flooding and erosion risks as well the amount of energy at dike infrastructure. The accumulated effect of seagrass under calm weather conditions is considered more important than the increased attenuation in absolute values it provides during extreme conditions. The overall conclusion is that seagrass expansion could be a useful addition to engineered coastal protection measures.

Corrigendum to “Large-scale nutrient and carbon dynamics along the river-estuary-ocean continuum” [Sci. Total Environ. 890 (2023) 164421] - Norbert Kamjunke; Holger Brix; Götz Flöser; Ingeborg Bussmann; Claudia Schütze; Eric P. Achterberg; Uta Ködel; Philipp Fischer; Louise Rewrie; Tina Sanders; Johannes Pein; Benjamin Jacob; et al. (Science of The Total Environment, 2023)

Honey bee drones are synchronously hyperactive inside the nest - Louisa C. Neubauer; Jacob D. Davidson; Benjamin Wild; David M. Dormagen; Tim Landgraf; Iain D. Couzin; Michael L. Smith (Animal Behaviour, 2023)

Environmental formation of methylmercury is controlled by synergy of inorganic mercury bioavailability and microbial mercury‐methylation capacity - Benjamin D. Peterson; David P. Krabbenhoft; Katherine D. McMahon; Jacob M. Ogorek; Michael T. Tate; William H. Orem; Brett A. Poulin (Environmental Microbiology, 2023)
Methylmercury (MeHg) production is controlled by the bioavailability of inorganic divalent mercury (Hg(II) i ) and Hg‐methylation capacity of the microbial community (conferred by the hgcAB gene cluster). However, the relative importance of these factors and their interaction in the environment remain poorly understood. Here, metagenomic sequencing and a full‐factorial MeHg formation experiment were conducted across a wetland sulfate gradient with different microbial communities and pore water chemistries. From this experiment, the relative importance of each factor on MeHg formation was isolated. Hg(II) i bioavailability correlated with the dissolved organic matter composition, while the microbial Hg‐methylation capacity correlated with the abundance of hgcA genes. MeHg formation responded synergistically to both factors. Notably, hgcA sequences were from diverse taxonomic groups, none of which contained genes for dissimilatory sulfate reduction. This work expands our understanding of the geochemical and microbial constraints on MeHg formation in situ and provides an experimental framework for further mechanistic studies.

Extreme temperature indices over the Volta Basin: CMIP6 model evaluation - Jacob Agyekum; Thompson Annor; Emmanuel Quansah; Benjamin Lamptey; Leonard Kofitse Amekudzi; Benjamin Kofi Nyarko (Climate Dynamics, 2023)

The sounds of a helicopter on Mars - Ralph D. Lorenz; Sylvestre Maurice; Baptiste Chide; David Mimoun; Alexander Stott; Naomi Murdoch; Martin Giller; Xavier Jacob; Roger C. Wiens; Franck Montmessin; Håvard Grip; Theodore Tzanetos; et al. (Planetary and Space Science, 2023)

Defining putative tertiary sulci in lateral prefrontal cortex in chimpanzees using human predictions - Catherine B. Hathaway; Willa I. Voorhies; Neha Sathishkumar; Chahat Mittal; Jewelia K. Yao; Jacob A. Miller; Benjamin J. Parker; Kevin S. Weiner (Brain Structure and Function, 2023)

Subtidal secondary circulation induced by eddy viscosity-velocity shear covariance in a predominantly well-mixed tidal inlet - Wei Chen; Benjamin Jacob; Arnoldo Valle-Levinson; Emil Stanev; Joanna Staneva; Thomas H. Badewien (Frontiers in Marine Science, 2023)
The secondary circulation in a predominantly well-mixed estuarine tidal inlet is examined with three-dimensional numerical simulations of the currents and density field in the German Bight. Simulations analyze two complete neap and spring tidal cycles, inspired by cross-section measurements in the tidal inlet, with a focus on subtidal time scales. The study scrutinizes the lateral momentum balance and quantifies the individual forces that drive the residual flow on the cross-section. Forces (per unit mass) from the covariance between eddy viscosity and tidal vertical shear (ESCO) play a role in the lateral momentum budget. During neap tide, the ESCO-driven flow is weak. Accelerations driven by advection dominate the subtidal secondary circulation, which shows an anti-clockwise rotation. During spring tide, the ESCO acceleration, together with the baroclinicity and centrifugal acceleration, drives a clockwise circulation (looking seaward). This structure counteracts the advection-induced flow, leading to the reversal of the secondary circulation. The decomposition of the lateral ESCO term contributors reveals that the difference in ESCO between neap and spring tides is attributed to the change in the vertical structure of lateral tidal currents, which are maximum near the bottom in spring tide. The findings highlight the role of the tidally varying vertical shears in the ESCO mechanism.

Land management drives dynamic changes to microbial function through edaphic factors and soil biota - Jacob R. Hopkins; Tatiana A. Semenova-Nelsen; Benjamin A. Sikes (Pedobiologia, 2023)

Hominoid-specific sulcal variability is related to face perception ability - Benjamin J. Parker; Willa I. Voorhies; Guo Jiahui; Jacob A. Miller; Ethan Willbrand; Tyler Hallock; Nicholas Furl; Lúcia Garrido; Brad Duchaine; Kevin S. Weiner (Brain Structure and Function, 2023)

Amplified drought trends in Nepal increase the potential for Himalayan wildfires - Binod Pokharel; Shankar Sharma; Jacob Stuivenvolt-Allen; Shih-Yu Simon Wang; Matthew LaPlante; Robert R. Gillies; Sujan Khanal; Michael Wehner; Alan Rhoades; Kalpana Hamal; Benjamin Hatchett; Wan-Yu Liu; et al. (Climatic Change, 2023)

Corrigendum to “Harmonization of acronyms for volatile organic compound metabolites using a standardized naming system” [Int. J. Hygiene Environ. Health 235 (2021) 113749] - Denise S. Tevis; Sharon R. Flores; Brandon M. Kenwood; Deepak Bhandari; Peyton Jacob; Jia Liu; Pawel K. Lorkiewicz; Daniel J. Conklin; Stephen S. Hecht; Maciej L. Goniewicz; Benjamin C. Blount; Víctor R. De Jesús (International Journal of Hygiene and Environmental Health, 2023)

Qualitative identification of volatile compounds in foods and flowers using passive headspace extraction with activated charcoal fabric - Venita Totten; Jacob Willis; Stefka Eddins; Benjamin Brooks (Food Research International, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Assessment of defoliation and subsequent growth losses caused by Lymantria dispar using terrestrial laser scanning (TLS) - Martin Jacobs; Torben Hilmers; Benjamin M. L. Leroy; Hannes Lemme; Sebastian Kienlein; Jörg Müller; Wolfgang W. Weisser; Hans Pretzsch (Trees, 2022)
Key message TLS scans of three surveys before, during and after gypsy moth gradation, allowed high-resolution tracking of defoliation and subsequent inter-annual growth losses on an individual tree level. Abstract Foliation strongly determines all tree growth processes but can be reduced by various stress factors. Insect defoliation starts at variable times and is one stress factor that may affect photosynthetic processes and cause immediate reactions like refoliation, which are difficult to detect by surveys repeated at 1-year intervals. This study used a large-scale field experiment in German oak/mixed forests affected by gypsy moths ( Lymantria dispar ) to test the use of terrestrial laser scanning (TLS) for detecting inter-annual foliation and growth losses at the individual tree level caused by the gypsy moth. The experiment comprised two levels of gypsy moth defoliation risk, high (H) and low (L), as well as two pest control treatment levels: spraying with the insecticide Mimic (M) or unsprayed control (C). The factorial design consisted of four treatment combinations (HC, HM, LC, and LM), applied to 11 spatial blocks with a total of 44 plots. The TLS approach detected the defoliation caused by the gypsy moth, estimated as leaf area and crown perforation parameters. For the first time, TLS-derived tree foliation was evaluated based on inter-annual stem growth. Leaf area and crown perforation showed a correlation of + 0.6 and – 0.35, respectively, with basal area increments. Furthermore, this study revealed subsequent growth losses in the same year due to defoliation. Our results show that TLS can offer new opportunities to develop new indicators that monitor foliation at the individual tree level. The crown perforation can describe defoliation or the tree’s vitality based on one scanning campaign, whereas the leaf area needed at least two.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Cryptofaunal diversity in fringing reef rhodoliths - Mira Abrecht; Viktor Nunes Peinemann; Ara Kevork Yazaryan; Madeline Kestler; Braden Charles DeMattei; Benjamin A. Hà; Emily Ryznar; David K. Jacobs (Coral Reefs, 2022)
Rhodolith distribution, morphology, and cryptofauna have been minimally studied on fringing reefs. We present the first study to examine both rhodolith distribution and associated cryptofauna in a tropical fringing reef, located along the microtidal, wave-dominated north shore of Moorea, French Polynesia. We find higher abundances of larger, rounder, and more branching rhodoliths in locations where longer waves impact the fringing reef. Among 1879 animals extracted and identified from 145 rhodoliths, ophiuroids, polychaetes, decapod crustaceans, and gastropods are most abundant, with a wide range of additional taxa contributing to diversity. Large and branching rhodoliths contain the greatest number and diversity of cryptofaunal organisms and are the preferred habitat of rigid-bodied, non-burrowing forms. Overall, exposure to waves entering the lagoon through passes appears to be a critical determinant of rhodolith abundance, morphotype, and in turn cryptofaunal composition in fringing reef habitats.

A Global Ocean Oxygen Database and Atlas for Assessing and Predicting Deoxygenation and Ocean Health in the Open and Coastal Ocean - Marilaure Grégoire; Véronique Garçon; Hernan Garcia; Denise Breitburg; Kirsten Isensee; Andreas Oschlies; Maciej Telszewski; Alexander Barth; Henry C. Bittig; Jacob Carstensen; Thierry Carval; Fei Chai; et al. (Frontiers in Marine Science, 2021)
In this paper, we outline the need for a coordinated international effort toward the building of an open-access Global Ocean Oxygen Database and ATlas (GO 2 DAT) complying with the FAIR principles (Findable, Accessible, Interoperable, and Reusable). GO 2 DAT will combine data from the coastal and open ocean, as measured by the chemical Winkler titration method or by sensors (e.g., optodes, electrodes) from Eulerian and Lagrangian platforms (e.g., ships, moorings, profiling floats, gliders, ships of opportunities, marine mammals, cabled observatories). GO 2 DAT will further adopt a community-agreed, fully documented metadata format and a consistent quality control (QC) procedure and quality flagging (QF) system. GO 2 DAT will serve to support the development of advanced data analysis and biogeochemical models for improving our mapping, understanding and forecasting capabilities for ocean O 2 changes and deoxygenation trends. It will offer the opportunity to develop quality-controlled data synthesis products with unprecedented spatial (vertical and horizontal) and temporal (sub-seasonal to multi-decadal) resolution. These products will support model assessment, improvement and evaluation as well as the development of climate and ocean health indicators. They will further support the decision-making processes associated with the emerging blue economy, the conservation of marine resources and their associated ecosystem services and the development of management tools required by a diverse community of users (e.g., environmental agencies, aquaculture, and fishing sectors). A better knowledge base of the spatial and temporal variations of marine O 2 will improve our understanding of the ocean O 2 budget, and allow better quantification of the Earth’s carbon and heat budgets. With the ever-increasing need to protect and sustainably manage ocean services, GO 2 DAT will allow scientists to fully harness the increasing volumes of O 2 data already delivered by the expanding global ocean observing system and enable smooth incorporation of much higher quantities of data from autonomous platforms in the open ocean and coastal areas into comprehensive data products in the years to come. This paper aims at engaging the community (e.g., scientists, data managers, policy makers, service users) toward the development of GO 2 DAT within the framework of the UN Global Ocean Oxygen Decade (GOOD) program recently endorsed by IOC-UNESCO. A roadmap toward GO 2 DAT is proposed highlighting the efforts needed (e.g., in terms of human resources).

Adenosine A2A receptor null chondrocyte transcriptome resembles that of human osteoarthritic chondrocytes - Cristina M. Castro; Carmen Corciulo; Benjamin Friedman; Zhi Li; Samson Jacob; David Fenyo; Bruce N. Cronstein (Purinergic Signalling, 2021)

Contrasting heat stress response patterns of coral holobionts across the Red Sea suggest distinct mechanisms of thermal tolerance - Christian R. Voolstra; Jacob J. Valenzuela; Serdar Turkarslan; Anny Cárdenas; Benjamin C. C. Hume; Gabriela Perna; Carol Buitrago‐López; Katherine Rowe; Monica V. Orellana; Nitin S. Baliga; Suman Paranjape; Guilhem Banc‐Prandi; et al. (Molecular Ecology, 2021)
Corals from the northern Red Sea, in particular the Gulf of Aqaba (GoA), have exceptionally high bleaching thresholds approaching >5℃ above their maximum monthly mean (MMM) temperatures. These elevated thresholds are thought to be due to historical selection, as corals passed through the warmer Southern Red Sea during recolonization from the Arabian Sea. To test this hypothesis, we determined thermal tolerance thresholds of GoA versus central Red Sea (CRS) Stylophora pistillata corals using multi‐temperature acute thermal stress assays to determine thermal thresholds. Relative thermal thresholds of GoA and CRS corals were indeed similar and exceptionally high (~7℃ above MMM). However, absolute thermal thresholds of CRS corals were on average 3℃ above those of GoA corals. To explore the molecular underpinnings, we determined gene expression and microbiome response of the coral holobiont. Transcriptomic responses differed markedly, with a strong response to the thermal stress in GoA corals and their symbiotic algae versus a remarkably muted response in CRS colonies. Concomitant to this, coral and algal genes showed temperature‐induced expression in GoA corals, while exhibiting fixed high expression (front‐loading) in CRS corals. Bacterial community composition of GoA corals changed dramatically under heat stress, whereas CRS corals displayed stable assemblages. We interpret the response of GoA corals as that of a resilient population approaching a tipping point in contrast to a pattern of consistently elevated thermal resistance in CRS corals that cannot further attune. Such response differences suggest distinct thermal tolerance mechanisms that may affect the response of coral populations to ocean warming.

Cardiac response to adrenergic stress differs by sex and across the lifespan - Aykhan Yusifov; Vikram E. Chhatre; Jacob M. Zumo; Ross F. Cook; Benjamin D. McNair; Emily E. Schmitt; Kathleen C. Woulfe; Danielle R. Bruns (GeroScience, 2021)

Understanding the Impact of Bathymetric Changes in the German Bight on Coastal Hydrodynamics: One Step Toward Realistic Morphodynamic Modeling - Benjamin Jacob; Emil V. Stanev (Frontiers in Marine Science, 2021)
The hydrodynamic response to morphodynamic variability in the coastal areas of the German Bight was analyzed via numerical experiments using time-referenced bathymetric data for the period 1982–2012. Time-slice experiments were conducted for each year with the Semi-implicit Cross-scale Hydroscience Integrated System Model (SCHISM). This unstructured-grid model resolves small-scale bathymetric features in the coastal zone, which are well-resolved in the high-resolution time-referenced bathymetric data (50 m resolution). Their analysis reveals the continuous migration of tidal channels, as well as rather complex change of the depths of tidal flats in different periods. The almost linear relationship between the cross-sectional inlet areas and the tidal prisms of the intertidal basins in the East Frisian Wadden Sea demonstrates that these bathymetric data describe a consistent morphodynamic evolutionary trend. The numerical experiment results are streamlined to explain the hydrodynamic evolution from 1982 to 2012. Although the bathymetric changes were mostly located in a relatively small part of the model area, they resulted in substantial changes in the M2 tidal amplitudes, i.e., larger than 5 cm in some areas. The hydrodynamic response to bathymetric changes largely exceeded the response to sea level rise. The tidal asymmetry estimated from the model appeared very sensitive to bathymetric evolution, particularly between the southern tip of Sylt Island and the Eider Estuary along the eastern coast. The peak current asymmetry weakened from 1982 to 1995 and even reversed within some tidal basins to become flood-dominant. This would suggest that the flushing trend in the 1980s was reduced or reversed in the second half of the studied period. Salinity also appeared sensitive to bathymetric changes; the deviations in the individual years reached ~22 psu in the tidal channels and tidal flats. One practical conclusion from the present numerical simulations is that wherever possible, the numerical modeling of near-coastal zones must employ time-referenced bathymetry data. The second, perhaps even more important conclusion, is that the progress of morphodynamic modeling in realistic ocean settings with multiple scales and varying bottom forms is strongly dependent on the availability of bathymetric data with appropriate temporal and spatial resolution.

A global reconnaissance of particulates and metals/metalloids in untreated drinking water sources - Jonathan W. Peterson; Benjamin M. Fry; Daniel R. Wade; Ford J. Fishman; Jacob T. Stid; Jonas M. Peterson; Cleveland E. Tarp; Randall D. Wade; Sarah A. Brokus; Michael J. Pikaart; Brent P. Krueger; Aaron A. Best (Environmental Monitoring and Assessment, 2021)
Metal and metalloid contamination in drinking water sources is a global concern, particularly in developing countries. This study used hollow membrane water filters and metal-capturing polyurethane foams to sample 71 drinking water sources in 22 different countries. Field sampling was performed with sampling kits prepared in the lab at Hope College in Holland, MI, USA. Filters and foams were sent back to the lab after sampling, and subsequent analysis of flushates and rinsates allowed the estimation of suspended solids and metal and other analayte concentrations in source waters. Estimated particulate concentrations were 0–92 mg/L, and consisted of quartz, feldspar, and clay, with some samples containing metal oxides or sulfide phases. As and Cu were the only analytes which occurred above the World Health Organization (WHO) guidelines of 10 μg/L and 2000 μg/L, respectively, with As exceeding the guideline in 45% of the sources and Cu in 3%. Except for one value of ~ 285 μg/L, As concentrations were 45–200 μg/L (river), 65–179 μg/L (well), and 112–178 μg/L (tap). Other metals (Ce, Fe, Mg, Mn, Zn) with no WHO guideline were also detected, with Mn the most common. This study demonstrated that filters and foams can be used for reconnaissance characterization of untreated drinking water. However, estimated metal and other analyte concentrations could only be reported as minimum values due to potential incomplete retrieval of foam-bound analytes. A qualitative reporting methodology was used to report analytes as “present” if the concentration was below the WHO guideline, and “present-recommend retesting” if the concentration was quantifiable and above the WHO guideline.

Sharing and reporting benefits from biodiversity research - Emily Marden; Richard J. Abbott; Frédéric Austerlitz; Daniel Ortiz‐Barrientos; Regina S. Baucom; Pim Bongaerts; Aurélie Bonin; Camille Bonneaud; Luke Browne; C. Alex Buerkle; Ana L. Caicedo; David W. Coltman; et al. (Molecular Ecology, 2021)

The Effect of Muscle Activation on Head Kinematics During Non-injurious Head Impacts in Human Subjects - Kristen A. Reynier; Ahmed Alshareef; Erin J. Sanchez; Daniel F. Shedd; Samuel R. Walton; Nicholas K. Erdman; Benjamin T. Newman; J. Sebastian Giudice; Michael J. Higgins; James R. Funk; Donna K. Broshek; Thomas J. Druzgal; et al. (Annals of Biomedical Engineering, 2020)

A 6.5‐kb intergenic structural variation enhances P450‐mediated resistance to pyrethroids in malaria vectors lowering bed net efficacy - Leon M. J. Mugenzi; Benjamin D. Menze; Magellan Tchouakui; Murielle J. Wondji; Helen Irving; Micareme Tchoupo; Jack Hearn; Gareth D. Weedall; Jacob M. Riveron; Fidelis Cho‐Ngwa; Charles S. Wondji (Molecular Ecology, 2020)
Elucidating the complex evolutionary armory that mosquitoes deploy against insecticides is crucial to maintain the effectiveness of insecticide‐based interventions. Here, we deciphered the role of a 6.5‐kb structural variation (SV) in driving cytochrome P450‐mediated pyrethroid resistance in the malaria vector, Anopheles funestus . Whole‐genome pooled sequencing detected an intergenic 6.5‐kb SV between duplicated CYP6P9a/b P450s in pyrethroid‐resistant mosquitoes through a translocation event. Promoter analysis revealed a 17.5‐fold higher activity ( p CYP6P9a/b for each SV genotype supported its role as an enhancer because SV+/SV+ homozygote mosquitoes had a significantly greater expression for both genes than heterozygotes SV+/SV− (1.7‐ to 2‐fold) and homozygotes SV−/SV− (4‐to 5‐fold). Designing a PCR assay revealed a strong association between this SV and pyrethroid resistance (SV+/SV+ vs. SV−/SV−; odds ratio [OR] = 2,079.4, p p

Frequent fire slows microbial decomposition of newly deposited fine fuels in a pyrophilic ecosystem - Jacob R. Hopkins; Jean M. Huffman; William J. Platt; Benjamin A. Sikes (Oecologia, 2020)

High-Resolution Estimation and Spatial Interpolation of Temperature Structure in the Atmospheric Boundary Layer Using a Small Unmanned Aircraft System - Benjamin L. Hemingway; Amy E. Frazier; Brian R. Elbing; Jamey D. Jacob (Boundary-Layer Meteorology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Inhibitory Control Deficits Associated with Upregulation of CB1R in the HIV-1 Tat Transgenic Mouse Model of Hand - Ian R. Jacobs; Changqing Xu; Douglas J. Hermes; Alexis F. League; Callie Xu; Bhupendra Nath; Wei Jiang; Micah J. Niphakis; Benjamin F. Cravatt; Ken Mackie; Somnath Mukhopadhyay; Aron H. Lichtman; et al. (Journal of Neuroimmune Pharmacology, 2019)

The PNPLA3 I148M variant promotes lipid-induced hepatocyte secretion of CXC chemokines establishing a tumorigenic milieu - Hans Dieter Nischalke; Philipp Lutz; Eva Bartok; Benjamin Krämer; Bettina Langhans; Regina Frizler; Thomas Berg; Jochen Hampe; Stephan Buch; Christian Datz; Felix Stickel; Gunther Hartmann; et al. (Journal of Molecular Medicine, 2019)

Subcortical shape and neuropsychological function among U.S. service members with mild traumatic brain injury - David F. Tate; Benjamin S. C. Wade; Carmen S. Velez; Ann Marie Drennon; Jacob D. Bolzenius; Douglas B. Cooper; Jan E. Kennedy; Matthew W. Reid; Amy O. Bowles; Paul M. Thompson; Boris A. Gutman; Jeffrey D. Lewis; et al. (Brain Imaging and Behavior, 2019)

The effects of enhanced attention and working memory on smooth pursuit eye movement - Jacob L. Stubbs; Sherryse L. Corrow; Benjamin Kiang; William J. Panenka; Jason J. S. Barton (Experimental Brain Research, 2018)

Insights into the Biodiversity, Behavior, and Bioluminescence of Deep-Sea Organisms Using Molecular and Maritime Technology - Steven Haddock; Lynne Christianson; Warren Francis; Séverine Martini; Meghan Powers; Casey Dunn; Philip Pugh; Claudia Mills; Karen Osborn; Brad Seibel; Anela Choy; Christine Schnitzler; et al. (Oceanography, 2017)

Political transition and emergent forest‐conservation issues in Myanmar - Graham W. Prescott; William J. Sutherland; Daniel Aguirre; Matthew Baird; Vicky Bowman; Jake Brunner; Grant M. Connette; Martin Cosier; David Dapice; Jose Don T. De Alban; Alex Diment; Julia Fogerite; et al. (Conservation Biology, 2017)
Political and economic transitions have had substantial impacts on forest conservation. Where transitions are underway or anticipated, historical precedent and methods for systematically assessing future trends should be used to anticipate likely threats to forest conservation and design appropriate and prescient policy measures to counteract them. Myanmar is transitioning from an authoritarian, centralized state with a highly regulated economy to a more decentralized and economically liberal democracy and is working to end a long‐running civil war. With these transitions in mind, we used a horizon‐scanning approach to assess the 40 emerging issues most affecting Myanmar's forests, including internal conflict, land‐tenure insecurity, large‐scale agricultural development, demise of state timber enterprises, shortfalls in government revenue and capacity, and opening of new deforestation frontiers with new roads, mines, and hydroelectric dams. Averting these threats will require, for example, overhauling governance models, building capacity, improving infrastructure‐ and energy‐project planning, and reforming land‐tenure and environmental‐protection laws. Although challenges to conservation in Myanmar are daunting, the political transition offers an opportunity for conservationists and researchers to help shape a future that enhances Myanmar's social, economic, and environmental potential while learning and applying lessons from other countries. Our approach and results are relevant to other countries undergoing similar transitions.

Interactions between wind and tidally induced currents in coastal and shelf basins - Benjamin Jacob; Emil Vassilev Stanev (Ocean Dynamics, 2017)

Infection risk decreases with increasing mismatch in host and pathogen environmental tolerances - A. Justin Nowakowski; Steven M. Whitfield; Evan A. Eskew; Michelle E. Thompson; Jonathan P. Rose; Benjamin L. Caraballo; Jacob L. Kerby; Maureen A. Donnelly; Brian D. Todd (Ecology Letters, 2016)
The fungal pathogen Batrachochytrium dendrobatidis ( Bd ) has caused the greatest known wildlife pandemic, infecting over 500 amphibian species. It remains unclear why some host species decline from disease‐related mortality whereas others persist. We introduce a conceptual model that predicts that infection risk in ectotherms will decrease as the difference between host and pathogen environmental tolerances (i.e. tolerance mismatch) increases. We test this prediction using both local‐scale data from Costa Rica and global analyses of over 11 000 Bd infection assays. We find that infection prevalence decreases with increasing thermal tolerance mismatch and with increasing host tolerance of habitat modification. The relationship between environmental tolerance mismatches and Bd infection prevalence is generalisable across multiple amphibian families and spatial scales, and the magnitude of the tolerance mismatch effect depends on environmental context. These findings may help explain patterns of amphibian declines driven by a global wildlife pandemic.

Local and remote response of the North Sea dynamics to morphodynamic changes in the Wadden Sea - Benjamin Jacob; Emil Vassilev Stanev; Yinglong Joseph Zhang (Ocean Dynamics, 2016)

Overview of Integrative Assessment of Marine Systems: The Ecosystem Approach in Practice - Angel Borja; Michael Elliott; Jesper H. Andersen; Torsten Berg; Jacob Carstensen; Benjamin S. Halpern; Anna-Stiina Heiskanen; Samuli Korpinen; Julia S. Stewart Lowndes; Georg Martin; Naiara Rodriguez-Ezpeleta (Frontiers in Marine Science, 2016)

A global meta‐analysis of the relative extent of intraspecific trait variation in plant communities - Andrew Siefert; Cyrille Violle; Loïc Chalmandrier; Cécile H. Albert; Adrien Taudiere; Alex Fajardo; Lonnie W. Aarssen; Christopher Baraloto; Marcos B. Carlucci; Marcus V. Cianciaruso; Vinícius de L. Dantas; Francesco de Bello; et al. (Ecology Letters, 2015)
Recent studies have shown that accounting for intraspecific trait variation ( ITV ) may better address major questions in community ecology. However, a general picture of the relative extent of ITV compared to interspecific trait variation in plant communities is still missing. Here, we conducted a meta‐analysis of the relative extent of ITV within and among plant communities worldwide, using a data set encompassing 629 communities (plots) and 36 functional traits. Overall, ITV accounted for 25% of the total trait variation within communities and 32% of the total trait variation among communities on average. The relative extent of ITV tended to be greater for whole‐plant (e.g. plant height) vs. organ‐level traits and for leaf chemical (e.g. leaf N and P concentration) vs. leaf morphological (e.g. leaf area and thickness) traits. The relative amount of ITV decreased with increasing species richness and spatial extent, but did not vary with plant growth form or climate. These results highlight global patterns in the relative importance of ITV in plant communities, providing practical guidelines for when researchers should include ITV in trait‐based community and ecosystem studies.

The interaction of escitalopram and R-citalopram at the human serotonin transporter investigated in the mouse - Jacob P. R. Jacobsen; Per Plenge; Benjamin D. Sachs; Alan L. Pehrson; Manuel Cajina; Yunzhi Du; Wendy Roberts; Meghan L. Rudder; Prachiti Dalvi; Taylor J. Robinson; Sharon P. O’Neill; King S. Khoo; et al. (Psychopharmacology, 2014)

Novel molecular determinants of viral susceptibility and resistance in the lipidome of E miliania huxleyi - James M. Fulton; Helen F. Fredricks; Kay D. Bidle; Assaf Vardi; B. Jacob Kendrick; Giacomo R. DiTullio; Benjamin A. S. Van Mooy (Environmental Microbiology, 2014)
Summary Viruses play a key role in controlling the population dynamics of algae, including E miliania huxleyi , a globally distributed haptophyte with calcite coccoliths that comprise ca. 50% of the sinking carbonate flux from the surface ocean. E miliania huxleyi viruses ( EhVs ) routinely infect and terminate E . huxleyi blooms. EhVs are surrounded by a lipid envelope, which we found to be comprised largely of glycosphingolipids ( GSLs ) with lesser amounts of polar glycerolipids. Infection appears to involve membrane fusion between the virus and host, and we hypothesized that specific polar lipids may facilitate virus attachment. We identified three novel intact polar lipids in E . huxleyi strain CCMP 374 and EhV 86, including a GSL with a monosaccharide sialic acid headgroup ( sGSL ); for all 11 E . huxleyi strains we tested, there was a direct relationship between sGSL content and sensitivity to infection by EhV 1, EhV 86 and EhV 163. In mesocosms, the E . huxleyi population with greatest initial sGSL content had the highest rate of virus‐induced mortality. We propose potential physiological roles for sGSL that would be beneficial for growth but leave cells susceptible to infection, thus furthering the discussion of R ed Q ueen‐based co‐evolution and the cost(s) of sensitivity and resistance in the dynamic E . huxleyi ‐ EhV system.

Resource depression, climate change, and mountain sheep in the eastern Great Basin of western North America - Jacob L. Fisher; Benjamin Valentine (Archaeological and Anthropological Sciences, 2013)

Various Anticoagulants and Fluoride do not Affect HbA1C Level - Maneesh Mailankot; Thushara Thomas; P. Praveena; Juliet Jacob; Jobin Rajan Benjamin; D. M. Vasudevan (Indian Journal of Clinical Biochemistry, 2012)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Quantifying stochastic error propagation in Bayesian parametric estimates using non-linear parameters of Anopheles gambiae s.l. habitats - Benjamin George Jacob; James Gunter; Erick Xavier Caamano; David Alexander Gathings; John Githure; James Larry Regens; Robert John Novak (International Journal of Remote Sensing, 2010)

Flood frequency analysis using historical data: accounting for random and systematic errors - Luc Neppel; Benjamin Renard; Michel Lang; Pierre-Alain Ayral; Denis Coeur; Eric Gaume; Nicolas Jacob; Olivier Payrastre; Karine Pobanz; Freddy Vinet (Hydrological Sciences Journal, 2010)

A rapid biochemical test to assess postharvest deterioration of sugarcane and milled juice - Gillian Eggleston; Jacob Karr; Anthony Parris; Benjamin Legendre (Sugar Tech, 2009)

Intercalated discs: multiple proteins perform multiple functions in non-failing and failing human hearts - Colleen B. Estigoy; Fredrik Pontén; Jacob Odeberg; Benjamin Herbert; Michael Guilhaus; Michael Charleston; Joshua W. K. Ho; Darryl Cameron; Cristobal G. dos Remedios (Biophysical Reviews, 2009)